Exploring the antecedents of entrepreneurial intentions an examination of global entrepreneurship monitor data - Schulz, Daniel Georg. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
The calls for new and innovative firms are growing louder, claiming entrepreneurs create jobs and boost the economy at the same time. This study examines the effects of unemployment and perceived opportunities and capabilities on entrepreneurial intentions. Previously, most research in this field focused on entrepreneurial activity instead and yielded contradicting outcome. The aim is to make use of the more direct relationship that can be drawn by employing entrepreneurial intentions instead of actual activity. Specifically, this study focuses on the relationship between unemployment and entrepreneurial intentions. Data from the Global Entrepreneurship Monitor and the World Bank for 92 countries and for the years between 2003 and 2018 are analyzed by conducting a multiple linear regression. The findings of this study show that unemployment rates are positively related to entrepreneurial intentions and so are increasing levels of perceived opportunities and capabilities. This study offers a new perspective on the discussion of the relationship between unemployment and entrepreneurship. The results indicate that the drivers of entrepreneurial intentions are numerous and yield relevant insights for policy makers to support them in their efforts to promote entrepreneurship and spur economic development.
Keywords: Entrepreneurship.